Nusyuz and Syiqaq in Islamic Law : Concept, Impact, and Methods of Settlement - Hanif, Hamdan Arief; Nasihin, Khoirun; Hamdani, Fahmi Fatwa Rosyadi Satria; Arie Rachmat Sunjoto (VRISPRAAK : International Journal of Law, 2023)
Domestic conflict is an unavoidable phenomenon in married life. In Islam, there are two main forms of conflict that can cause disharmony in the family, namely nusyuz and syiqaq. Nusyuz refers to the defiance of one of the parties, either the husband or the wife, in carrying out their obligations in accordance with Islamic law. Meanwhile, syiqaq refers to a prolonged irreconcilable dispute between a married couple. This study aims to analyse the concepts of nusyuz and syiqaq as well as their settlement methods based on the perspective of Islamic law. This study uses a normative approach by examining the Qur'anic arguments, hadith, and the opinions of scholars. The results show that Islam regulates the steps of resolving nusyuz through advice, bed separation, and light sanctions with the aim of improving the relationship between husband and wife. In the case of shiqaq, Islam emphasises the importance of mediation through the appointment of hakam (peacemakers) from both parties before divorce becomes the last resort. By understanding the concepts and methods of conflict resolution in marriage according to Islam, it is hoped that married couples can be wiser in dealing with differences and prioritise fair and maslahat solutions for both parties.